PENANGANAN SAMPAH SECARA SWADAYA DI DESA PAKRAMAN CELUK, SUKAWATI, GIANYAR - I Gede Suartika (Bumi Lestari Journal of Environment, 2011)
The life of community must be supported by clean environment. It means that rubbish should be well and seriously managed. Rubbish management influences the cleanliness and the health of the environment because it risks to human health and even to their life. Households contribute the biggest amount of rubbish produced in customary villages. The negative impact of rubbish has a great influence on human life, particularly on people’s health. In addition to health, the other negative impacts of rubbish are the bad smell effecting the environment and the rubbish heap effecting the bad view so that a dirty environment leaves the feeling of inconvenience. Since the customary village contributes to the biggest amount of rubbish, it is necessary to give a better understanding concerning the impact of rubbish to the people living in customary villages. By giving a deeper understanding, the customary village community in Bali will be able to manage rubbish. There are some kinds of rubbish produced. They are organic and unorganic rubbish. This rubbish must be separated and then recycled to be more valuable things. Good rubbish management in customary villages will make the environment convenient for the tourist. As a result, the programs of the government intended to increase the number of tourist visit can be successful. This is because Bali is promoted to other countries for its beauty, friendly people, and culture which is supported by the clean government. The success of tourism industry makes the level people’s economy and the amount of foreign exchange increase either for local and national government. For that reason, the efforts supporting the tourism industry must be strengthened.